Economic dynamics of global energy geopolitics - Ikiz, Ahmet Salih, 1968- (Engineering Science Reference, 2018)
"This book explores the geopolitical importance of the energy suppliers in region's economic substructure due to the energy supply and demand in world order. It provides how this global phenomenon affects countries' economies with certain implementation of energy demand and supply in world markets. It also provides knowledge and information about possible international policy formations"--